Loss to follow‐up in the hepatitis C care cascade: A substantial problem but opportunity for micro‐elimination. Issue 12 (22nd September 2020) - van Dijk, Marleen; Drenth, Joost P.H.
Abstract: Since the advent of direct‐acting antivirals, elimination of hepatitis C viral (HCV) infections seems within reach. However, studies on the HCV cascade of care show suboptimal progression through each step for all patient groups. Loss to follow‐up (LTFU) is a major issue and is a barrier to HCV elimination. This review summarizes the scale of the LTFU problem and proposes a micro‐elimination approach. Retrieving LTFU patients and re‐engaging them with care again has shown to be feasible in the Netherlands. Micro‐elimination through retrieval can contribute to reaching the World Health Organization's viral hepatitis elimination targets by 2030.